(untitled) (Research, Society and Development, 2021)
The responsibility of the agricultural sector to produce food effectively also seeks to meet this demand in a sustainable manner, generating safe products for the final consumer. Cysticercosis, fasciolosis and hydatidosis are zoonoses. Human infection occurs due to the ingestion of rare or poorly washed foods containing infectious forms of these parasites, which can cause several damages to the health of those affected. The objective of this work was to establish the occurrence of these three diseases in sheep and cattle originating in municipalities in the area covered by the 12th Regional Supervision of the Department of Inspection of Products of Animal Origin (DIPOA) of SEAPDR-RS, slaughtered under state inspection in the period from January 2018 to December 2019. In this period, a total of 227,946 cattle were slaughtered, 113,907 in 2018 and 114,039 in 2019, counting animals of different age categories. The average rate of occurrence considering the period was 0.75% for cysticercosis, 49.14% for fasciolosis and 16.22% for hydatidosis. The total number of slaughtered sheep was 45,695, of which, 23,746 in 2018 and 21,949 in 2019. The occurrences of diseases in this species, considering the average for the period, were 0.86% for cysticercosis, 0.63% for fasciolosis and 11.62% for hydatidosis. It is concluded that, in this study period, fasciolosis presented the highest occurrence in cattle and hydatidosis in sheep. The data evaluated in this article serve as a tool for public health actions and show the importance of the Official Inspection Services and the veterinary doctor in obtaining safe food.